Case Report: Clinical pharmacist prescriber in depression treatment in primary care settings: clinical case focused on prescribing practice - Stuhec, Matej (Frontiers in Psychiatry, 2025)
IntroductionPharmacotherapy of depression represents a significant challenge in the management of depression in primary care. Although effective treatments have been available, many patients are still not adequately managed. Clinical pharmacists represent one of the possible strategies in the management, although this practice is rarely seen outside the United Kingdom and the United States.AimThe aim of the case was to evaluate the impact of clinical pharmacist prescribers on depression treatment.MethodsA longitudinal, observational, case-based medication review by a pharmacist prescriber was conducted for a 63-year-old Slovenian patient in a primary care ambulatory setting. The review included three structured medication review assessments performed by a clinical pharmacist prescriber at defined intervals: first observation, two months post-intervention, and six months after first observation. The pharmacists conducted medication reviews and prescribed medications like physicians, operating within a collaborative practice agreement as dependent prescribers. Predefined outcomes included diabetes management (HbA1c and blood glucose), lipid levels (S-LDL), pain (Visual Analogue Scale [VAS]), depression (Patient Health Questionnaire-9 [PHQ-9]), and quality of life (assessed via EQ-5D-VAS). The patient’s complete medication regimens were reviewed, focusing on dosage appropriateness, indication matching, potential drug-drug interactions, and medication adherence.ResultsA 63-year-old male Slovenian patient diagnosed with depression, type 2 diabetes with polyneuropathy, and hypothyroidism underwent two medication reviews between December 2024 and July 2025. The pharmacist prescribed amitriptyline and semaglutide (accepted by the patient’s physician). Notable improvements were observed in glycemic control (HbA1c reduced from 9.9% to 8.2%), and quality of life (EQ-5D-VAS score improved from 30/100 to 80/100). Depression symptoms also resolved, with the PHQ-9 score improving from 11 to 4.ConclusionsThis case study demonstrates that interventions by a clinical pharmacist prescriber during the medication review process resulted in improved clinical outcomes in the treatment of depression, as well as enhanced quality of life. It represents an important contribution to the development of pharmacist prescribing roles in depression management within primary care settings outside of the United Kingdom and the United States.